2016
DOI: 10.1007/s00464-016-5175-4
|View full text |Cite
|
Sign up to set email alerts
|

Current status of laparoscopy for acute abdomen in Italy: a critical appraisal of 2012 clinical guidelines from two consecutive nationwide surveys with analysis of 271,323 cases over 5 years

Abstract: The surveys showed an increasing use of laparoscopy for patients with abdominal emergencies. The 2012 national guidelines profoundly influenced the Italian surgical practice in the laparoscopic approach to the acute abdomen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 38 publications
(31 reference statements)
1
12
0
1
Order By: Relevance
“…[10,11] Moreover, LA has been shown to be safer in complicated AA than in open surgery; therefore, its use in the emergency setting is rising. [12][13][14][15][16] While challenging, discrimination between uncomplicated and complicated AA is clinically relevant as outcomes vary, with complicated cases faring worse. [17] Additionally, patients with uncomplicated AA may be successfully treated with antibiotics, in comparison to complicated cases, which practically always require an appendectomy.…”
Section: Introductionmentioning
confidence: 99%
“…[10,11] Moreover, LA has been shown to be safer in complicated AA than in open surgery; therefore, its use in the emergency setting is rising. [12][13][14][15][16] While challenging, discrimination between uncomplicated and complicated AA is clinically relevant as outcomes vary, with complicated cases faring worse. [17] Additionally, patients with uncomplicated AA may be successfully treated with antibiotics, in comparison to complicated cases, which practically always require an appendectomy.…”
Section: Introductionmentioning
confidence: 99%
“…Based on our clinical observations, we can say that we have come a long way in the selection and performance of laparoscopy. In their well-attended survey on surgeons in Italy, Agresta et al [11] reported that laparoscopy is increasingly being used in acute abdominal surgeries performed in the period of 2010-2014.…”
Section: Discussionmentioning
confidence: 99%
“…Se ha demostrado su seguridad y beneficios también en pacientes con cuadros agudos abdominales. De hecho, el abordaje laparoscópico en la emergencia es capaz de proporcionar una mejor visión de toda la cavidad abdominal con un trauma mínimo dando la posibilidad de realizar un diagnóstico preciso y al mismo tiempo un tratamiento definitivo (10) . Las ventajas de la cirugía miniinvasiva son particularmente atractivas en la emergencia y su uso ha ido en aumento en los últimos diez años (10,11) .…”
Section: Discussionunclassified